Effects of climate change and land use/cover changes on carbon sequestration in forest ecosystems in the coastal area of China - Zhen, Yanlin; Zhang, Xiuying; Zhang, Congguo; Gao, Qian; Dong, Jiaqi; Zhang, Liuzhen; Lu, Xuehe; Wang, Yingying (Frontiers in Forests and Global Change, 2023)
Introduction Climate change and land use/cover changes (LUCC) greatly influenced terrestrial carbon sequestration. Methods This study evaluated the effects of climate change and LUCC on the carbon sequestration of forest ecosystems from 1991 to 2020 in the coastal area of China using a process-based global vegetation dynamic model (IBIS). Results and discussion The results showed that temperature had an increasing trend, with a rate of 0.02 °C yr−1; 20.00% of the forest coverage shifted spatially but there was only a 0.31% increase in total area. The carbon sequestration amounts by plants (net primary productivity, NPP) and the net carbon budget (net ecosystem productivity, NEP) in the coastal area of China in 2020 were 666.49 and 58.45 Tg C yr−1, respectively, which increased by 18.31% and 2509.30%, respectively, compared to the values in 1991. The increased forest ecosystem NPP and NEP were mainly due to climate change, while forest cover changes increased NPP by only 0.06% and NEP by 9.75% with a strong regional difference. The NPP showed a significant increasing trend, with a rate of 3.01 Tg C yr−1, which was positively correlated with temperature (0.43, p < 0.01) and precipitation (0.42, p < 0.01). However, the NEP largely varied during 1991-2020 and did not show a significant correlation with precipitation or temperature. These results provide scientific guidance for the government to enact environmental protection and low-carbon land use planning policies.